2020
DOI: 10.32859/era.20.4.1-15
|View full text |Cite
|
Sign up to set email alerts
|

Hyphaene compressa, an important palm in the arid and semi-arid regions of Kenya

Abstract: Background: Peasant agroecosystems in Kenya are considered to be a continuum of integrated traditional farming systems and natural ecosystem conservancy programs. Hyphaene compressa (doum palm) exists in arid and semi-arid lands (ASAL) of Kenya. While research in these areas is focusing on new plants to be brought to the areas, there is no focus on doum palm, which is already adapted to these areas. Scanty ethnobotanical knowledge exists in the form of unpublished material. The study aimed to determine domesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…These accessions also exhibited reciprocal monophyly based on phylogenetic analysis. This corroborates the phenotypic diversity studies on H. compressa where accessions from Kwale exhibited the highest phenotypic diversity compared to other regions (Omire et al, 2020b).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These accessions also exhibited reciprocal monophyly based on phylogenetic analysis. This corroborates the phenotypic diversity studies on H. compressa where accessions from Kwale exhibited the highest phenotypic diversity compared to other regions (Omire et al, 2020b).…”
Section: Discussionsupporting
confidence: 90%
“…There is scanty information on the genetic diversity of doum palm which limits access to its important traits and thus hinders its improvement. Previous diversity studies on H. compressa focussed on accessing the variability of its morphological traits (Omire et al, 2020b). The study identified five morphotypes with accessions from the Kenyan Coastal area being the most heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…The materials produced from H. thebaica are almost entirely made by the Afar women. A similar report revealed the same pattern in east Africa, particularly Djibouti (Stauffer et al 2018;Omire et al 2020).…”
Section: Materials Culturementioning
confidence: 55%
“…These include basketry, shelter, rope, farming tools, fencing, etc. (Woodward 2007;Ryan 2011;Addis et al 2013;Stauffer et al 2018;Abdel-Raman 2019;Sulieman & Mariod 2019;Omire et al 2020). Although the study of plant material culture received little attention than other themes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing interest in doum palm domestication in some of the arid and semi-arid regions of Kenya. The drive for this is the decline in doum palm germplasm resources in these areas due to human interference and biotic stress [ 8 ]. H. compressain situ conservation is found in six protected areas and five ex situ conservation areas globally [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%